Downside Risk Measurement of Indonesian Financial and Energy Securities: A Value at Risk Perspective - Rony, Zahara Tussoleha; Jefri, Riny; Rusmardiana, Ana; Pramono, Susatyo Adhi; Mamadiyarov, Zokir (Journal of Applied Science, Engineering, Technology, and Education, 2025)
This study explores the measurement of downside risk in the Indonesian capital market by applying Value at Risk (VaR) analysis to two representative companies from different economic sectors: PT Asuransi Bina Dana Arta Tbk (ABDA), an insurance firm, and PT ABM Investama Tbk (ABMI), an energy and mining company. Utilizing daily return data from December 2023 to November 2024, we assess both individual and portfolio-level risk profiles through a quantitative framework based on Monte Carlo simulation. Our findings reveal distinct risk-return characteristics between the two stocks. ABDA exhibits a negative average daily return (-0.15%) with relatively low volatility (standard deviation of 1.12%), whereas ABMI shows a positive expected return (0.07%) but higher variability (standard deviation of 2.06%). Interestingly, despite its lower volatility, ABDA records higher VaR values across all confidence levels, indicating greater downside exposure—particularly evident at the 95% confidence level where ABDA's one-day VaR is -2.04%, compared to ABMI’s -1.77%. A cross-sector portfolio consisting of 40% ABDA and 60% ABMI demonstrates meaningful diversification benefits, reducing the standard deviation to 1.02% and improving the VaR to -1.54%. This represents a risk reduction of 24.5% compared to ABDA alone and 13% relative to ABMI alone. For a hypothetical investment of IDR 100 million, these improvements equate to reduced potential daily losses of IDR 508,258 and IDR 233,504 respectively. The results emphasize that strategic cross-sector allocation—even within a simple two-asset portfolio—can significantly enhance risk-adjusted performance in emerging markets like Indonesia. By combining financial and energy assets with differing sensitivities to macroeconomic conditions, investors can better manage downside risk while maintaining exposure to diverse economic drivers. This research provides a practical methodology for risk assessment and portfolio construction, offering valuable insights for asset managers and decision-makers operating in volatile and multi-sector investment environments.